2020
DOI: 10.1105/tpc.19.00695
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Regulates Sucrose Transport to Repress Petal Abscission in Rose (Rosa hybrida)

Abstract: Developmental transitions in plants require adequate carbon resources, and organ abscission often occurs due to competition for carbohydrates/assimilates. Physiological studies have indicated that organ abscission may be activated by sucrose deprivation; however, an underlying regulatory mechanism that links sucrose transport to organ shedding has yet to be identified. Here, we report that transport of sucrose and the phytohormone auxin to petals through the phloem of the abscission zone (AZ) decreases during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 76 publications
1
53
0
Order By: Relevance
“…carbon and nitrogen compound shortage caused by phloem flux arrest, or/and by internal hormonal factors (ethylene, JA, ABA). A recent report provided a link between metabolism and the mechanisms of auxin and ethylene regulated abscission [118]. The report demonstrated that auxin regulates sucrose transport during rose petal abscission, antagonistically to ethylene induced abscission.…”
Section: Common Organ Abscission Genes and Processes Of Eudicots Andmentioning
confidence: 98%
“…carbon and nitrogen compound shortage caused by phloem flux arrest, or/and by internal hormonal factors (ethylene, JA, ABA). A recent report provided a link between metabolism and the mechanisms of auxin and ethylene regulated abscission [118]. The report demonstrated that auxin regulates sucrose transport during rose petal abscission, antagonistically to ethylene induced abscission.…”
Section: Common Organ Abscission Genes and Processes Of Eudicots Andmentioning
confidence: 98%
“…Usually, the balance between ethylene and auxin plays a crucial role in the shedding process [ 1 ]. Besides, the lack of carbohydrates can also contribute to the abscission of plant organs [ 7 , 15 ]. Consequently, genes that synthesize these phytohormones and signal transduction pathways also play a key role in the plant organ abscission mechanism [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organ abscission is crucial for the natural development of plant parts, such as leaves, flowers, and fruits (Aloni et al, 1997 ; Gómez‐Cadenas et al, 2000 ; Reichardt et al, 2020 ; Zhu et al, 2011 ). Many studies have observed that organ abscission is often induced by competition for carbohydrates, reflected in “early flower drop” in many plants (Gómez‐Cadenas et al, 2000 ; Liang et al, 2020 ). Abscission is not always negative: The “June drop” seen in fruit tree cultivars can help apple growers avoid the negative impact of excessive fruit bearing (McFadyen et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%